The Effects of the Team-Game-Tournaments Learning Model on Primary School: Basic Dribble Moves in Basketball Games - Prasetyo, Tri; Sir, Irvan; Amir, Atmam (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The objective of this study should be to examine how MIS Islamiyah Nidhomiyah students in Pasuruan, East Java, can enhance their basketball dribbling skills. This research approach involves collaborating with collaborators, researchers, and students in a classroom setting to undertake action research. Cycle II is where actions are taken. The students' average score was 65 after assessing the data on the results of the pre-action ball dribbling test in a basketball game using the Team Games Tournament (TGT) method, 10 students completed the test and five did not. Cycle I had an average score of 73 students, with 9 students finishing and 6 students failing. In Cycle II, the average number of students is 81, with as many as 14 students completing and one student failing to complete. Based on the findings of the implementation of the TGT cooperative learning model in basketball dribbling from pre-action, cycle I, and cycle II, it is reasonable to conclude that learning outcomes improved greatly in students of MIS Islamiyah Nidhomiyah, Rejoso District, Pasuruan.